1994
DOI: 10.1007/bf01664932
|View full text |Cite
|
Sign up to set email alerts
|

Levels of prostaglandin E2 and leukotriene B4 in tears of vernal conjunctivitis patients during a therapeutic trial with indomethacin

Abstract: A therapeutic trial of 1% indomethacin (Indoptic) eye drops was carried out in 21 children. Looking for possible mediators of inflammation in vernal conjunctivitis, prostaglandin E2 (PGE2) and leukotriene B4 (LTB4 levels in the tears of 9 patients were measured and the effect of the treatment on them examined. A control group of 10 unaffected children was added. Out of 42 eyes in which indomethacin treatment was instilled, only 17 remained in treatment through a 6-week follow-up period. In a few of them a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…However, it has been reported that systemic bromfenac treatment significantly reduces not only PGE 2 and PGF 2 α levels in the follicular fluid, but also LTB 4 levels compared with those after placebo treatment in humans [25]. The LTB 4 level in tears of patients with VKC is reported to be elevated [26]. We have recently reported that the tear LTB 4 level in AD patients with ocular complications showed a significant elevation compared with that in AD patients without ocular complications and controls [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that systemic bromfenac treatment significantly reduces not only PGE 2 and PGF 2 α levels in the follicular fluid, but also LTB 4 levels compared with those after placebo treatment in humans [25]. The LTB 4 level in tears of patients with VKC is reported to be elevated [26]. We have recently reported that the tear LTB 4 level in AD patients with ocular complications showed a significant elevation compared with that in AD patients without ocular complications and controls [4].…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] It has been demonstrated that leukotrienes are also produced in the conjunctiva 37 and are detectable in tear fluids of patients affected by allergic conjunctivitis including VKC. [38][39][40] Indeed LT concentration in tears increases in allergic subjects following allergen challenge. 41,42 In addition, conjunctival administration of LTB4, as well as LTC4 and LTD4, induces vessel vasodilatation, oedema, hyperaemia, and leucocyte and eosinophilic infiltration of the conjunctiva.…”
Section: Vernal Keratoconjunctivitis S Bonini Et Al 346mentioning
confidence: 99%
“…These mediators may contribute to the pathogenesis of VKC through several mechanisms. The oedema observed in VKC is related to the activity of LTs and PGs in inducing a conjunctival microvascular permeability increase that remains virtually constant over time even in very small doses [3,17,19,20].…”
Section: Discussionmentioning
confidence: 99%